1993
DOI: 10.1079/bjn19930041
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of volatile fatty acids from the rumen of lactating dairy cows as influenced by volatile fatty acid concentration, pH and rumen liquid volume

Abstract: The effect of rumen liquid volume, pH and concentration of volatile fatty acids (VFA) on the rates of absorption of acetic, propionic and butyric acids from the rumen was examined in lactating dairy cows. Experimental solutions introduced into the emptied, washed rumen comprised two different volumes (10 or 30 I), four levels of pH (4.5, 5.4, 6.3, 7.2) and three levels of individual VFA concentrations (20, SO or 100 mM-acetic, propionic or butyric acid). All solutions contained a total of 170 mM-VFA and an osm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
136
6
12

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(165 citation statements)
references
References 23 publications
(50 reference statements)
11
136
6
12
Order By: Relevance
“…In the current study, ruminal total SCFA concentration, which does not necessarily reflect the rate of production as absorption and passage are not accounted for (Dijkstra et al, 1993), was greater (118 v. 95 mM) in cattle fed LF compared with HF. In addition, the greater ruminal osmolality in LF-than HF-fed cattle reflected the changes in total SCFA concentration that could be attributed to a greater ruminal supply of rapidly fermentable CHO as a result of higher dietary starch content and DMI.…”
Section: Discussioncontrasting
confidence: 61%
“…In the current study, ruminal total SCFA concentration, which does not necessarily reflect the rate of production as absorption and passage are not accounted for (Dijkstra et al, 1993), was greater (118 v. 95 mM) in cattle fed LF compared with HF. In addition, the greater ruminal osmolality in LF-than HF-fed cattle reflected the changes in total SCFA concentration that could be attributed to a greater ruminal supply of rapidly fermentable CHO as a result of higher dietary starch content and DMI.…”
Section: Discussioncontrasting
confidence: 61%
“…This can originate in differences between VFA in their fractional absorption rate (C2 , C3 , C4, Bergman, 1990) and from the differential effect of pH on the absorption rates of the VFA. This effect increases with chain length (Dijkstra et al, 1993), as a function of pKa (Pitt et al, 1996;Noziè re and Hoch, 2006). Despite good within-experiment relationships between the VFA profiles in the production and the VFA profiles in the rumen fluid, inter-experiment variability remained high, particularly for C4.…”
Section: Discussionmentioning
confidence: 95%
“…Despite good within-experiment relationships between the VFA profiles in the production and the VFA profiles in the rumen fluid, inter-experiment variability remained high, particularly for C4. To assess whether different absorption rates may explain the differences across studies, we performed dynamic simulations of rumen VFA pools, with VFA fractional absorption rates depending on rumen pH (estimated from VFA concentration if not reported in the publications), VFA concentration and rumen volume (Dijkstra et al, 1993;Noziè re and Hoch, 2006). The simulations suggested that the differences in pH, VFA concentrations or rumen volume were insufficient to explain the differences between production and concentration profiles across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, absorption rates of VFA across the rumen wall may have been increased at night due to a lower rumen fluid volume, resulting in a higher effective surface area for absorption (Dijkstra et al, 1993). Small increases in the VFA pool immediately after the beginning of grazing are expected due to a low efficiency of chewing during eating (Boudon et al, 2006;Acosta et al, 2007).…”
Section: Resultsmentioning
confidence: 99%